Produção de semente de soja na região de Alto Graças - MT - Goulart, Daniel de Brito (2007)
The aim of efficiency in the production and commercialization of soybean seed is what keeps a company in the competitive seed market. The crop of a harvest was planned two years before, when the seed fields were installed. So, the planning of the whole process of seed production, from the installation of the fields, going through the crop production, processing, storage and commercialization, until the final result, that it is the crop of the grains originated from these commercial seeds, all those are part of the sophisticated system of seed production, where the efficiency aim in all of the processes determines the profitability and the permanence of the company in business. This way the aim of the present study was to analyze the indexes of efficiency in production and commercialization of soybean seed at Sementes Arco-Íris company, located in the district of Alto Garças -MT. The variables used were utilization of fields, moisture at harvesting, physiologic quality during the storage, approval of lots for the commercialization and commercialization efficiency. The results showed that: 1- The good utilization of fields is variable according to cultivar and crop year, obtaining an average of 32.9%; 2- Seed drying is necessary for most of the production, this procedure could reach to 100% for some cultivar; 3- The UBS productivity was low, it could be considered 70%; 4- The germination reduces in 2.6 percentile points from April to September while the average of emergence in soil was reduced 3.2 p.p. there are differences among the cultivar for the storage potential; 5- It is reached more than 90% of commercialization of the approved volume, occurring variations from 64,7% to 100% of commercialization, mainly in function of the offer and demand of the specific cultivars for each crop year